If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + 2y + -13 = 11y + -11 + -3y Reorder the terms: 32 + -13 + 2y = 11y + -11 + -3y Combine like terms: 32 + -13 = 19 19 + 2y = 11y + -11 + -3y Reorder the terms: 19 + 2y = -11 + 11y + -3y Combine like terms: 11y + -3y = 8y 19 + 2y = -11 + 8y Solving 19 + 2y = -11 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 19 + 2y + -8y = -11 + 8y + -8y Combine like terms: 2y + -8y = -6y 19 + -6y = -11 + 8y + -8y Combine like terms: 8y + -8y = 0 19 + -6y = -11 + 0 19 + -6y = -11 Add '-19' to each side of the equation. 19 + -19 + -6y = -11 + -19 Combine like terms: 19 + -19 = 0 0 + -6y = -11 + -19 -6y = -11 + -19 Combine like terms: -11 + -19 = -30 -6y = -30 Divide each side by '-6'. y = 5 Simplifying y = 5
| 8(7-9)-8=-16(p-2) | | a*d+c=90 | | x^2+9x-3240=0 | | 5+2x=2x+n | | 4h-3=6k+5 | | 4/2=2 | | 4/2=6 | | 14-4a=4a-10 | | 6x-23=-23+5x | | 198=86+7x | | 6(w-1)+21=3(3w+5) | | Y+13=2(x-8) | | 4t-15=-11+8t | | x^2+14x+38=5 | | 3(y-7)=10y | | 6c=9x-3 | | 160+4m=125 | | 0.5n+6=6 | | -(12-a)= | | Y-11=(x-6) | | 5x^2-20x=10x-45 | | 8x+5x+4+8=9x+4+3x | | 50n+6=6 | | 4.9x^2+10x-70=0 | | 3(3+5x)-1=38 | | 17-7x=6+5x | | -(2-a)= | | 11=-2x-4 | | 4.9x^2+10x-60=0 | | (1-x)(1-x)-4=0 | | -2x-1(-4x-14)=8 | | 5ax+5b=9cx+d |